Alpha-1 Antitrypsin Augmentation and the Liver Phenotype of Adults With Alpha-1 Antitrypsin Deficiency (Genotype Pi∗ZZ) - Fromme, Malin; Hamesch, Karim; Schneider, Carolin V; Mandorfer, Mattias; Pons, Monica; Thorhauge, Katrine H; Pereira, Vitor; Sperl, Jan; Frankova, Sona; Reichert, Matthias C; Benini, Federica; Burbaum, Barbara; et al. (Clinical gastroenterology and hepatology, 2024)
BACKGROUND & AIMS: α1-Antitrypsin (AAT) is a major protease inhibitor produced by hepatocytes. The most relevant AAT mutation giving rise to AAT deficiency (AATD), the 'Pi∗Z' variant, causes harmful AAT protein accumulation in the liver, shortage of AAT in the systemic circulation, and thereby predisposes to liver and lung injury. Although intravenous AAT augmentation constitutes an established treatment of AATD-associated lung disease, its impact on the liver is unknown. METHODS: Liver-related parameters were assessed in a multinational cohort of 760 adults with severe AATD (Pi∗ZZ genotype) and available liver phenotyping, of whom 344 received augmentation therapy and 416 did not. Liver fibrosis was evaluated noninvasively via the serum test AST-to-platelet ratio index and via transient elastography-based liver stiffness measurement. Histologic parameters were compared in 15 Pi∗ZZ adults with and 35 without augmentation. RESULTS: Compared with nonaugmented subjects, augmented Pi∗ZZ individuals displayed lower serum liver enzyme levels (AST 71% vs 75% upper limit of normal, P < .001; bilirubin 49% vs 58% upper limit of normal, P = .019) and lower surrogate markers of fibrosis (AST-to-platelet ratio index 0.34 vs 0.38, P < .001; liver stiffness measurement 6.5 vs 7.2 kPa, P = .005). Among biopsied participants, augmented individuals had less pronounced liver fibrosis and less inflammatory foci but no differences in AAT accumulation were noted. CONCLUSIONS: The first evaluation of AAT augmentation on the Pi∗ZZ-related liver disease indicates liver safety of a widely used treatment for AATD-associated lung disease. Prospective studies are needed to confirm the beneficial effects and to demonstrate the potential efficacy of exogenous AAT in patients with Pi∗ZZ-associated liver disease.
Keywords: SERPINA1; deficit alfa1-antitrypsinu; fenotyp; Liver Fibrosis; alpha 1-Antitrypsin Deficiency; genotyp; lidé; Fibroscan; Adult; α(1)-Antitrypsin Deficiency; Pi∗Z; Phenotype; dospělí; Humans; Liver Cirrhosis; jaterní cirhóza; Augmentation Therapy; Genotype